Hepatoprotective Effect of Pomegranate (Punica Granatum) Fruit Juice and Seed Extracts against CCL4-Induced Toxicity: Hepatoprotective effect of pomegranate extracts - Akram Jamshidzadeh; Hossein Niknahad; Marjan Abbasian; Abbas Rezaeian Mehrabadi (Iranian Journal of Pharmaceutical Sciences, 2012)
Punica granatum is used as a medicinal plant, and its fruit concentrate has been used for the prevention and treatment of liver diseases in Iran. The effects of different concentrations of the hydroalcoholic, ethyl acetate and n-hexane extracts of the Punica granatum (fruit juice and seed) were investigated against CCl4-induced cytotoxicity in HepG2 cells. Concentrations (1-10000 μg/ml) of the extracts were added to the cells, 1 h before the addition of 100 mM of CCl4. After 24 h, the cells were evaluated for toxicity, TBARs level and GSH content. The hydroalcoholic extracts of fruit juice and seeds with concentrations of 100 to 1000 μg/ml protected the cells against CCl4 induced cytotoxicity, but the ethyl acetate extract of fruit juice with higher concentration (1000 μg/ml) protected the cells against CCl4 cytotoxicity and the n-hexane extracts were less effective. The ethyl acetate and n-hexane extracts of seeds with different concentrations did not have any significant protective effect. The Punica granatum extracts themselves were not toxic towards cells with concentrations up to 1 mg/ml. Therefore, the results of the present study are somehow consistent with traditional beliefs about hepatoprotective effects of Punica granatum.